2014
DOI: 10.1007/s00216-014-8264-z
|View full text |Cite
|
Sign up to set email alerts
|

Partition coefficients of organic compounds between water and imidazolium-, pyridinium-, and phosphonium-based ionic liquids

Abstract: The partition coefficients, P IL/w, of several compounds, some of them of biological and pharmacological interest, between water and room-temperature ionic liquids based on the imidazolium, pyridinium, and phosphonium cations, namely 1-octyl-3-methylimidazolium hexafluorophosphate, N-octylpyridinium tetrafluorophosphate, trihexyl(tetradecyl)phosphonium chloride, trihexyl(tetradecyl)phosphonium bromide, trihexyl(tetradecyl)phosphonium bis(trifluoromethylsulfonyl)imide, and trihexyl(tetradecyl)phosphonium dicyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 30 publications
0
10
0
1
Order By: Relevance
“…Aimed at developing guidelines for efficient processes, theoretical studies as well as phase diagrams for multiphasic systems were investigated in detail. Experimental and theoretical studies were performed by Rabari et 190 Coutinho and co-workers reported phase diagrams for a series of ionic 192 In particular, the latter PIL was immobilised in alginate capsules and used for the removal of Cd(II) from HCl aqueous solutions. 193 In a study by Soto and co-workers, the liquidliquid equilibria of a ternary system comprising water, n-dodecane and [P 66614 ][Ntf 2 ] were determined.…”
Section: Extraction and Separation Technologies Based On Pilsmentioning
confidence: 99%
“…Aimed at developing guidelines for efficient processes, theoretical studies as well as phase diagrams for multiphasic systems were investigated in detail. Experimental and theoretical studies were performed by Rabari et 190 Coutinho and co-workers reported phase diagrams for a series of ionic 192 In particular, the latter PIL was immobilised in alginate capsules and used for the removal of Cd(II) from HCl aqueous solutions. 193 In a study by Soto and co-workers, the liquidliquid equilibria of a ternary system comprising water, n-dodecane and [P 66614 ][Ntf 2 ] were determined.…”
Section: Extraction and Separation Technologies Based On Pilsmentioning
confidence: 99%
“…PB-RTILs are made of tetraalkylphosphonium cations with different anions and have some additional advantages compared to the nitrogen-based RTILs (NB-RTILs), such as very high thermal and chemical stability, higher solvation properties and they are cheaper [18]. There are about 20 different types of PB-RTILs commercially available.…”
Section: Introductionmentioning
confidence: 99%
“…As a counterpart, due to the typical high viscosities of the RTILs, a dilution with solvents such as methanol or acetonitrile can be necessary before injection into the HPLC column, which decreases the enrichment factor [18].…”
Section: Introductionmentioning
confidence: 99%
“…As harmless solvents in contrast to conventional organic solvents, ILs have attracted attention because of their special features such as high thermal stability, negligible volatility, and selective solubility. ILs have been applied for extraction and separation of bioactive compounds of hydrophobic 3-indole-butyric acid, ferulic acid and caffeine acid found in plants [7][8][9][10][11][12][13]. Magnetic ILs such as benzyltrioctylammonium bromotrichloroferrate (III) and 1,12-di(3-hexadecylbenzimidazolium) dodecane bis[(trifluoromethyl)-sulfonyl]imide bromotrichloroferrate (III) have higher extraction efficiencies for DNA molecules [14].…”
Section: Introductionmentioning
confidence: 99%